2010
DOI: 10.1007/s13244-009-0007-x
|View full text |Cite
|
Sign up to set email alerts
|

The future role of radiology in healthcare

Abstract: Rapidly evolving changes in the way that healthcare is administered, coupled with the amazing recent advances within imaging, has necessitated a review of the way in which radiology should be regarded. This review considers some aspects of these changes and offers some recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 11 publications
0
46
0
Order By: Relevance
“…This is presumably one of the principal reasons for the extensive usage of teleradiology services in both these countries. In the UK, both national and international providers are able to provide teleradiology services [7]. In Germany these services are still limited to nights, weekends and vacations, although the German regulations allow an expansion under certain circumstances [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is presumably one of the principal reasons for the extensive usage of teleradiology services in both these countries. In the UK, both national and international providers are able to provide teleradiology services [7]. In Germany these services are still limited to nights, weekends and vacations, although the German regulations allow an expansion under certain circumstances [25].…”
Section: Discussionmentioning
confidence: 99%
“…In other institutions, teleradiology is used for providing remote, off-hour radiological coverage; for emergency readings and to a lesser extent for subspecialty readings [5]. In the past decade, several national and international commercial teleradiology providers have emerged in Europe, facilitating the outsourcing of diagnostic readings [3, 7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Over the past 25 to 30 years radiology has changed dramatically as advances and improvements in imaging acquisition devices and telecommunications have occurred. Additionally, public expectations in response to these changes have changed, contributing to increased radiologist sub-specialization [ 1 , 2 ]. A significant consequence of this sub-specialization is increased utilization and growth of teleradiology, as referring clinicians and patients expect and often demand expert interpretation of images not only in major urban areas, but also in areas that are rural and medically underserved.…”
Section: Introductionmentioning
confidence: 99%
“…A significant consequence of this sub-specialization is increased utilization and growth of teleradiology, as referring clinicians and patients expect and often demand expert interpretation of images not only in major urban areas, but also in areas that are rural and medically underserved. Thus, teleradiology is perhaps the most successful and well-established telemedicine service, with over 70% of radiology practices in the United States (U.S.) using on-call emergency reporting, and general teleradiology being provided regularly by Nighthawk services around the world [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A poor radiographic technique, in turn, may lead to unnecessary exposures to X-radiation, poor image quality, repeated views and examinations, patient discomfort or further injury because of poor positioning and the possibility of a missed diagnosis or misdiagnosis. 16 Furthermore, a rapid shift from conventional to fully digitized radiology departments, along with rapidly evolving changes in healthcare administration 17 entails knowledgeable, up-to-date radiographers who utilize the technology. 18 Except for very limited number of studies that have described radiographers' self-reported competency 7,16 and the level of awareness pertaining to the protection against radiation, 19,20 to the best of our knowledge, there is no study in the literature regarding radiographers' level of knowledge with a dedicated focus on technical parameters and safety in plain radiography.…”
mentioning
confidence: 99%